Detection of Arcobacter species in different intestinal compartments of broiler chicken during slaughter and processing. Issue 10 (24th August 2020) - Schönknecht, Antje; Alter, Thomas; Gölz, Greta
Abstract: Arcobacter spp. are commonly present on meat products. However, the source of contamination on chicken meat is under dispute. Since different studies reported contradictory results on the occurrence of Arcobacter spp. inside the intestinal tract of chicken, our study examined four intestinal compartments at four significant production steps during broiler slaughter and processing in the slaughterhouse. Altogether, 157 intestinal tracts from 19 flocks were examined qualitatively and semiquantitatively applying a selective enrichment. Further verification was performed by mPCR and rpoB sequencing. Arcobacter spp. were only detected sporadically in intestinal contents after bleeding (2/32) and in none after scalding (0/32). After defeathering, Arcobacter spp. were detected in 62% (18/29) of the intestinal contents with 28% (8/29) of the duodenal, 21% (6/29) of the jejunal, 3% (1/29) of the cecal, and 55% (16/29) of the colonic samples tested positive with loads up to 24, 000 MPN/g in the colonic content. Further 88% (7/8) of colonic tissue samples were tested positive. After evisceration, the prevalences (58/64) and loads of Arcobacter spp. display comparable levels in the intestinal contents like after defeathering. In conclusion, our data point out that Arcobacter spp. are most likely detected in the colonic intestinal compartment of the chicken after defeathering and evisceration. Therefore, not only cross‐contamination originating from the environment inside the slaughterhouse may cause carcass contamination with Arcobacter spp. on broiler chicken carcasses. The detection of Arcobacter spp. in duodenal and jejunal contents as well as in the colonic tissue indicates that there possibly exists an Arcobacter reservoir inside the chicken. Abstract : Arcobacter spp. are commonly present on chicken meat products, and since cross‐contamination most probably takes places in the chicken slaughterhouse, we examined 157 intestinal tracts from 19 flocks at four significant production steps during broiler slaughter and processing in the slaughterhouse. Our data point out that Arcobacter spp. are most likely detected in the colonic intestinal compartment of the chicken after defeathering and evisceration, but the detection of Arcobacter spp. in duodenal and jejunal contents as well as in the colonic tissue indicates that not only cross‐contamination originating from the environment inside the slaughterhouse may cause contamination with Arcobacter spp. on chicken carcasses.